The Importance of Codification of Administrative Procedure for the Protection of Individual Rights in Kazakhstan - Aiym Szajachmetova (Acta Universitatis Lodziensis Folia Iuridica)
The article is an attempt to assess the functioning of the Code of Administrative Procedure of the Republic of Kazakhstan of 2020 in practice after 3 years of its application. A characteristic feature of this Code is that it covers both the proceedings of administrative bodies and proceedings before administrative courts, and its purpose is to raise the level of quality of public administration, as well as to consolidate the principles of judicial control of administration. The author draws attention to the strengths of this legal act, so important during the period of intensive systemic transformation in Kazakhstan. Its most important advantages include codification of general principles of procedure and definition of basic normative concepts. At the same time, she indicates a number of shortcomings of the legal regulation. She considers the most important to be the leaving of some disputes in the field of public law within the jurisdiction of ordinary courts. She sees an insufficient level of legal protection, in particular, in cases of administrative penalties for administrative offenses that have not been covered by the regulation of the Code of Administrative Procedure, despite their administrative nature.